A Closer Look at the Psychometric Properties of the Revised Children's Manifest Anxiety Scale–Second Edition Among U.S. Elementary and Secondary School Students. (September 2014) - Lowe, Patricia A.
The psychometric properties of the Revised Children's Manifest Anxiety Scale–Second Edition (RCMAS-2) were examined in a sample of 1, 003 U.S. elementary and secondary students in Grades 2 to 12. Confirmatory factor analyses (CFAs) were performed comparing the five-factor (target) model consisting of three anxiety (Physiological Anxiety, Social Anxiety, and Worry) factors and two defensiveness (Defensiveness 1 and 2) factors with a three-factor model (one anxiety factor and two defensiveness factors). The results of the CFAs conducted indicated that the five-factor model provided a better fit to the data than the three-factor model. Tests of measurement invariance were also performed and the results provided support for configural, metric, and partial scalar invariance of the RCMAS-2 scores across gender. Latent mean analyses were also conducted and the results of these analyses indicated that females scored significantly higher than males on the three anxiety factors. These findings provide support for the construct validity of the RCMAS-2 scores. Implications of the findings for mental health professionals who work with elementary and secondary school students are discussed.